Prejudice about stroke survivors in the workplace - Zhu, Bing, author; Gibbons, Alyssa M., advisor (Colorado State University. Libraries, 2016)
Recovering from a major health challenge, such as a cancer diagnosis or a stroke, is difficult in itself, but survivors may face additional obstacles in returning to work beyond their physical health. A recent study by Martinez, White, Shapiro, & Hebl (2015) found that cancer survivors are perceived as a warmer, but less competent, than normal employees in the workplace, and that job applicants who disclosed a history of cancer were treated less well and were less likely to be called back for an interview. This high-warmth/low-competence stereotype profile is often associated with paternalistic prejudice (Fiske, Cuddy Glick, and Xu, 2002). We replicated and extended Martinez and colleagues' study by comparing perceptions of cancer survivors and stroke survivors. We conducted an anonymous online survey in which participants rated how they think others would perceive stroke survivors in the workplace. This approach has been used successfully in the past to identify shared stereotypes while avoiding social desirability effects. We expected that stroke survivors would be perceived as warmer than other widely stereotyped social groups (Fiske et al.), but as even less competent than cancer survivors.
Perceptions of health challenges in the workplace
Keywords: stroke survivors; self-esteem; hope; rehabilitation